Design and Build Seawater Temperature and pH Measuring Equipment Microcontroller-Based - Pasaribu, Roberto Patar; Roni Sewiko; Iftinan Nabila; Ismail, R.Moh; Soeprijadi, Liliek (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2025)
The quality of water in a body of water has a very important role in supporting the survival and sustainability of the organisms that live in it. One of the important indicators of seawater quality is the physical and chemical parameters, including seawater temperature and pH. Temperature is a measure of the energy of molecular movement that plays a crucial role in regulating biological processes and the distribution of organisms. Meanwhile, variations in pH values can cause changes and imbalances in CO₂ levels that may endanger marine ecosystems. The purpose of this research is to design and develop a microcontroller-based seawater temperature and pH measuring device using a DS18B20 temperature sensor and a 4502C pH sensor. The results show that the device can detect water quality parameters in real time with an average accuracy of 99% when compared to standard measuring instruments. This research concludes that the designed device is effective, reliable, and easy to use for monitoring seawater quality. The implication of this study is that it can provide a low-cost and practical solution for environmental monitoring, support sustainable marine resource management, and be further developed into an integrated system for wider applications.